Spatiotemporal Patterns and Regional Transport Contributions of Air Pollutants in Wuxi City - Mao Mao; Xiaowei Wu; Yahui Zhang (Atmosphere)
In recent years, with the rapid socioeconomic development of Wuxi City, the frequent occurrence of severe air pollution events has attracted widespread attention from both the local government and the public. Based on the real-time monitoring data of criteria pollutants and GDAS (Global Data Assimilation System) reanalysis data, the spatiotemporal variation patterns, meteorological influences, and potential sources of major air pollutants in Wuxi across different seasons during 2019 (pre-COVID-19) and 2023 (post-COVID-19 restrictions) are investigated using the Pearson correlation coefficient, potential source contribution function (PSCF), and concentration-weighted trajectory (CWT) models. The results demonstrate that the annual mean PM2.5 concentration in Wuxi decreased significantly from 39.6 μg/m3 in 2019 to 29.3 μg/m3 in 2023, whereas the annual mean 8h O3 concentration remained persistently elevated, with comparable levels of 104.6 μg/m3 and 105.0 μg/m3 in 2019 and 2023, respectively. The O3 and particulate matter (PM) remain the most prominent air pollutants in Wuxi’s ambient air quality. The hourly mass concentrations of criteria pollutants, except O3, exhibited characteristic bimodal distributions, with peak concentrations occurring post-rush hour during morning and evening commute periods. In contrast, O3 displayed a distinct unimodal diurnal pattern, peaking between 15:00 and 16:00 local time. The spatial distribution patterns revealed significantly elevated concentrations of all monitored species, excluding O3, in the central urban zone, compared to the northern Taihu Lake region. The statistical analysis revealed significant correlations among PM concentrations and other air pollutants. Additionally, meteorological parameters exerted substantial influences on pollutant concentrations. The PSCF and CWT analyses revealed distinct seasonal variations in the potential source regions of atmospheric pollutants in Wuxi. In spring, the Suzhou–Wuxi–Changzhou metropolitan cluster and northern Zhejiang Province were identified as significant contributors to PM2.5 and O3 pollution in Wuxi. The potential source regions of O3 are predominantly distributed across the Taihu Lake-rim cities during summer, while the eastern urban agglomeration adjacent to Wuxi serves as major potential source areas for O3 in autumn. In winter, the prevailing northerly winds facilitate southward PM2.5 transport from central-northern Jiangsu, characterized by high emissions (e.g., industrial activities), identifying this region as a key potential source contribution area for Wuxi’s aerosol pollution. The current air pollution status in Wuxi City underscores the imperative for implementing more stringent and efficacious intervention strategies to ameliorate air quality.